2015
DOI: 10.1007/s10661-015-4674-4
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular and respiratory mortality attributed to ground-level ozone in Ahvaz, Iran

Abstract: Ahvaz, the capital city of Khuzestan Province, which produces Iran's most oil, is on the rolls of fame in view of air pollution. It has also suffered from dust storm during the recent two decades. So, emissions from transportation systems, steel, oil, black carbon, and other industries as anthropogenic sources and dust storm as a new phenomenon are two major concerns of air pollution in Ahvaz. Without any doubt, they can cause many serious problems for the environment and humans in this megacity. The main obje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 87 publications
(37 citation statements)
references
References 45 publications
1
33
0
1
Order By: Relevance
“…Some other studies, using human volunteers, identified that exposure to ozone could cause adverse systemic inflammation and cardiac autonomic effects through changes in heart rate variability and C-reactive protein, and thus contribute to cardiovascular mortality [7,10]. Though the mechanism is not conclusive yet, elevated ozone concentration could lead to respiratory and cardiovascular diseases according to many epidemiological studies [2][3][4][32][33][34][35]. Our study came to a similar conclusion, with identified susceptible groups being the elderly and males.…”
Section: Discussionsupporting
confidence: 82%
“…Some other studies, using human volunteers, identified that exposure to ozone could cause adverse systemic inflammation and cardiac autonomic effects through changes in heart rate variability and C-reactive protein, and thus contribute to cardiovascular mortality [7,10]. Though the mechanism is not conclusive yet, elevated ozone concentration could lead to respiratory and cardiovascular diseases according to many epidemiological studies [2][3][4][32][33][34][35]. Our study came to a similar conclusion, with identified susceptible groups being the elderly and males.…”
Section: Discussionsupporting
confidence: 82%
“…Khuzestan province has an area of 63,238 km 2 . Ahvaz is the capital of this province and it is located in the Middle East, between 48°and 29' east of the Greenwich meridian, 31°and 45' minutes north of the equator (20)(21)(22)(23)(24)(25)(26)(27)(28)(29). The location of Khuzestan province in the southwest of Iran is presented in Figure 1.…”
Section: Methodsmentioning
confidence: 99%
“…Ahvaz city, with a population of 1 million approximately, the capital of Khuzestan province is located between 48 to 49°and 29 min of the eastern longitude in the Greenwich meridian and 30 to 32°and 45 min of the northern latitude from the equator (Dobaradaran et al 2016;Geravandi et al 2015d;Goudarzi et al 2015a;Zallaghi et al 2014b).…”
Section: Geographical Features Of Ahvazmentioning
confidence: 99%